RefRec+: Six Degree-of-Freedom Estimation for Smartphone Using Floor Reflecting Light - Sugimoto, Masanori; Shimada, Shota; Hashizume, Hiromichi (Frontiers in Computer Science, 2022)
This paper describes a novel visible light positioning (VLP) system called RefRec+ allowing to estimate the six degree-of-freedom (6DoF) of a smartphone. In most existing VLP systems, their front camera faces multiple light sources installed at different places on a ceiling to detect their direct signals. To overcome the problem of the limited field of views that causes failure to capture required numbers of light sources for positioning and that of the high computational complexity because of image processing to a large-sized pixel data, RefRec+ captures indirect lights from the light sources reflected via a floor. RefRec+ estimates the 2-D position of a point of interest (POI) by calculating the received signal strength of individual light sources using the floor image captured by the camera. Using 2-D positions of multiple POIs and the angle of arrival method, RefRec+ obtains the 6DoF of the smartphone. Several experiments to confirm the performance of RefRec+ were conducted. Experimental results in a room measuring 4.0 m × 4.0 m using nine POIs each of which consists of 32 × 32 pixels in a captured image showed that the absolute errors at the 90th percentile for the 3-D coordinates were 0.2073 m, 0.1713 m, and 0.002464 m along the X, Y, and Z axes, respectively, and for the pitch, roll, and yaw angles were 5.78 degrees, 5.69 degrees, and 3.96 degrees, respectively.